Hubungan Antara Kematangan Kepribadian Dengan Gaya Hidup Hedonis Pada Mahasiswi - Afian, Dinayanti; , Drs. Soleh Amini Yahman, M.Si, Psi (2016)
Hedonistic lifestyle is an activity carried out by someone to achieve a pleasure and tend to enjoy the life of the world. One of the factors that influence the hedonistic lifestyle is a personality where the maturity of personality included into the aspect of personality. This study aims to determine the relationship between the maturity of ersonality with a hedonistic lifestyle, the maturity level of personality, the level of hedonistic lifestyle on the female students and the effective contribution from the maturity of the personality towards hedonistic lifestyle. Researcher used quantitative method to achieve the objectives of this research. The subjects used in this study are the students in Muhammadiyah University of Surakarta with total 100 female students. The results of the correlation coefficient (r) of -0.725 with a significance (p) = 0.000 (p <0.01). This indicates there is a significant negative relationship between of personality maturity with hedonistic lifestyle. Based on the results analysis, it shows hedonistic lifestyle variables have the empirical mean (RE) of 137.25 and the hypothetical mean (RH) of 122.5 which means the hedonistic lifestyle behaviorof research subjectsconsidered high. The maturity of personality variables have the empirical mean (RE) of 119.19 and the hypothetical mean (RH) of 125 which means thematurity of personality the research subjects classified as moderate. The effective contributiontowards hedonistic lifestyle is fromthe maturity of the personality with the value 52,5% it means there are other factors of 47,5 % affecting hedonistic lifestyle